Long-term weight loss maintenance for obesity: a multidisciplinary approach - Montesi L (Dove Medical Press, 2016)
Luca Montesi,1 Marwan El Ghoch,2 Lucia Brodosi,1 Simona Calugi,2 Giulio Marchesini,1 Riccardo Dalle Grave2 1Unit of Metabolic Diseases, S Orsola-Malpighi Hospital, “Alma Mater Studiorum” University, Bologna, Italy; 2Department of Eating and Weight Disorders, Villa Garda Hospital, Verona, Italy Abstract: The long-term weight management of obesity remains a very difficult task, associated with a high risk of failure and weight regain. However, many people report that they have successfully managed weight loss maintenance in the long term. Several factors have been associated with better weight loss maintenance in long-term observational and randomized studies. A few pertain to the behavioral area (eg, high levels of physical activity, eating a low-calorie, low-fat diet; frequent self-monitoring of weight), a few to the cognitive component (eg, reduced disinhibition, satisfaction with results achieved, confidence in being able to lose weight without professional help), and a few to personality traits (eg, low novelty seeking) and patient–therapist interaction. Trials based on the most recent protocols of lifestyle modification, with a prolonged extended treatment after the weight loss phase, have also shown promising long-term weight loss results. These data should stimulate the adoption of a lifestyle modification-based approach for the management of obesity, featuring a nonphysician lifestyle counselor (also called “lifestyle trainer” or “healthy lifestyle practitioner”) as a pivotal component of the multidisciplinary team. The obesity physicians maintain a primary role in engaging patients, in team coordination and supervision, in managing the complications associated with obesity and, in selected cases, in the decision for drug treatment or bariatric surgery, as possible more intensive, add-on interventions to lifestyle treatment. Keywords: obesity, lifestyle modification, cognitive behavior therapy, multidisciplinary treatment